SYNTHESIS, SPECTROSCOPIC CHARACTERIZATION AND BIOLOGICAL STUDIES OF 2-[(2-hydroxy-5-methoxyphenyl)methylidene]amino nicotinic acid AND ITS Iron (II) COMPLEXES - Osigbemhe, I. G.; Khan, M. E.; Amos, O.; Kabiru, H. D. (FUDMA JOURNAL OF SCIENCES, 2021)
Iron (II) complexes of 2-[(2-hydroxy-5-methoxyphenyl) methylidene]amino nicotinic acid derived from o-phenylenediamine and 5- methoxysalicaldehyde were synthesized and characterized by elemental analysis, using UV-Visible, IR, 1HNMR, 13CNMR, They were screened against known disease causative microbes to establish their effectiveness and efficacies as antimicrobial agents compared with national standards drugs, ampiclox and ketoconazole. Results showed that, the Schiff base exhibits antimicrobial action against all the bacteria and most of the fungi with exception of Candidas. albicans which exhibited naught diameter zone of inhibition. It was also found that the synthesized Schiff base exhibited two digits purity range, implying that it is relatively stable. The metal complex was found to be more susceptible in overall biological activity than the Schiff base synthesized and studied due to their structural stability in relationship to its activity. This has opened another drug window for the remedy to human diseases caused by these microbes